2011
DOI: 10.1111/j.1468-3083.2011.04070.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study comparing low‐dose liposomal amphotericin B with N‐methyl glucamine for the treatment of American cutaneous leishmaniasis

Abstract: Liposomal amphotericin B seems to be promising and safe for the treatment of American cutaneous leishmaniasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…For the treatment of the localized form of American cutaneous leishmaniasis, a study comparing lowdose liposomal amphotericin B (total dose of 7.5 mg/kg) with N-methyl glucamine showed that only 50% of patients achieved a clinical cure in the liposomal amphotericin B group, in comparison with a 100% clinical cure in the N-methyl glucamine group. 20 For the ML treatment, the World Health Organization guidelines recommend a total dose of 40-60 mg/kg, but we think that an intermediate dose can be used, according to our findings and the results reported in other studies. 15 We used a mean total dose of 32.5 mg/kg (range = 18.2-55.2 mg/kg) with a good cure rate.…”
Section: Discussionmentioning
confidence: 50%
“…For the treatment of the localized form of American cutaneous leishmaniasis, a study comparing lowdose liposomal amphotericin B (total dose of 7.5 mg/kg) with N-methyl glucamine showed that only 50% of patients achieved a clinical cure in the liposomal amphotericin B group, in comparison with a 100% clinical cure in the N-methyl glucamine group. 20 For the ML treatment, the World Health Organization guidelines recommend a total dose of 40-60 mg/kg, but we think that an intermediate dose can be used, according to our findings and the results reported in other studies. 15 We used a mean total dose of 32.5 mg/kg (range = 18.2-55.2 mg/kg) with a good cure rate.…”
Section: Discussionmentioning
confidence: 50%
“…The Leishmania species responsible for infection were identified in most studies (Table 1) [69][77], [81] The follow-up time ranged from 3 months to 1 year. Six references did not comply with eligibility criteria and were excluded [78][80], [82]–[84].…”
Section: Resultsmentioning
confidence: 99%
“…Pentavalent antimonials (meglumine antimoniate and sodium estibogluconate), amphotericin B (AMB) and miltefosine are the main drugs used for treatment of leishmaniasis, and the pentavalent antimony is the more common leishmanicidal drug used nowadays. Its parenteral use and associated adverse reactions decrease therapy compliance, and failure to antimony treatment is on rise in ATL [ 14 16 ]. AMB is the most effective drug for the treatment of leishmaniasis but its adverse reactions, mainly kidney injury, limit its use [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%